Comparison of external stents and DJ stents techniques for pediatric pyeloplasty: A systematic review and meta-analysis - Meng, Chunyang; Gan, Lijian; Li, Kangsen; Peng, Lei; Li, Jinze; Yang, Junbao; Li, Yunxiang (Frontiers in Pediatrics, 2022)
Objective To evaluate and compare the efficacy and safety between an external stent and a Double J stent for pediatric Pyeloplasty. Methods Through a systematical search of multiple scientific databases in July 2022, we performed a systematic review and meta-analysis of the primary outcomes of interest according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), whose protocol was registered with PROSPERO(CRD42021274087). Results Eleven studies involving 1,758 patients were included. No significant differences were observed in operative time (MD: 2.26; 95% CI −9.62 to 14.14; P = 0.79), operative success rate (OR: 1.10; 95% CI 0.57 to 2.10; P = 0.780), length of hospital stay (MD: 0.65; 95% CI −0.04 to 1.34; P = 0.063), or complications (OR: 0.87; 95%CI 0.48 to 1.56; P = 0.630) between external stents and DJ stents in pediatric pyeloplasty. According to the subgroup analysis, we found the external stent group had a shorter operative time than the DJ stent group in terms of robot-assisted laparoscopic pyeloplasty (MD: −17.13; 95% CI −32.8 to −1.45; P = 0.032). Conclusions There were no significant differences in operative time, operative success rate, length of hospital stay, or complications between external stents and DJ stents in pediatric pyeloplasty. The external stented procedure seemed to have less operative time when using robot-assisted laparoscopic pyeloplasty. However, due to the limitations of our analysis, more studies are still required to support our conclusion. Systematic review registration This systematic review has been registered on PROSPERO, the registration ID is CRD42021274087.